Synthesis and electrochemical investigations of ABPBI grafted montmorillonite based polymer electrolyte membranes for PEMFC applications. (February 2021) - Altaf, Faizah; Batool, Rida; Gill, Rohama; Rehman, Zohaib Ur; Majeed, Hammad; Ahmad, Adnan; Shafiq, Muhammad; Dastan, Davoud; Abbas, Ghazanfar; Jacob, Karl
Abstract: A series of novel poly (2, 5-benzimidazole)-grafted montmorillonite (ABPBI-MMT) and sulfonated poly vinyl alcohol (SPVA) composite membranes have been prepared via solution casting method which were further doped with phosphoric acid. The structure of composite membranes has been studied using FTIR, XRD and SEM. The effect of ABPBI-MMT on the water uptake (WU), proton conductivity, mechanical and chemical stability of the resultant membranes has been examined before and after phosphoric acid (PA) doping. This study flaunted that the introduction of ABPBI-MMT into SPVA decreased the WU of pristine polymer matrix as a result of acid-base interaction between the sulfonic acid and benzimidazole groups. However, after PA doping, the WU of the membranes has tremendously boosted. Initially, the influence of ABPBI grafted clay on proton conductivities of SPVA membranes has been studied along with the analysis of PA doping effect on membrane conductivity with fuel cell performance. Furthermore, the proton conductivities of PA doped, and un-doped composite membranes have been studied at high temperatures ranging from 100 to 140 °C under 0% RH. The PA-doped composite membranes show enhanced conductivity values (0.0075 Scm −1 ) at 140 °C even with 0% RH. The maximum proton conductivity of 0.157 Scm −1 and peak power density of 1100 mWcm −2 have been obtained at 140 °C under 100% RH with 15PBMPP composite membranes. These results indicate that the newly prepared PA-doped PEMs are an excellent candidates for high-temperature PEM fuel cell application. Graphical abstract: Image 1 Highlights: Novel ABPBI-MMT/SPVA composite PEMs have been prepared. FTIR and XRD and SEM were used for structural and morphological characterizations. ABPBI-MMT/SPVA composite PEMs showed enhanced proton conductivity. The maximum peak power density of 1100 mWcm-2 was obtained at 140 °C under 100% RH. ABPBI-MMT/SPVA PEMs could be an effectual alternative to high-priced PFSA PEMs.